Clocks and chronogeometry: rotating spacetimes and the relativistic null hypothesis - Menon, T; Linnemann, N; Read, J (Oxford University Press, 2018)
Recent work in the physics literature demonstrates that, in particular classes of rotating spacetimes, physical light rays in general do not traverse null geodesics. Having presented this result, we discuss its philosophical significance, both for the clock hypothesis (and, in particular, a recent purported proof thereof for light clocks), and for the operational meaning of the metric field.